Efectividad de un programa educativo en el nivel de conocimiento sobre alimentación saludable en madres de preescolar - Castañeda Otoya, Kattya Guissell (2018)
The present investigation is of quantitative, pre-experimental type, was carried out with the purpose of determining the effectiveness of the Educational Program "Cultivating a Healthy Eating" in the level of knowledge about feeding in the mothers of the initial Educational Institution Nº 1639. The sample was consolidated by 37 mothers. For data collection, the questionnaire was used to determine the level of knowledge about feeding in preschool mothers, an elaboration that was prepared by the authors taking into account the bases MINSA (2014), MINSA (2016) and Cortez (2008). For the analysis of the variables, the T-student test was used. The following results were found: Before applying the Educational Program, 16 percent of the mothers obtained a deficient level of knowledge about healthy eating; 73 percent, a level of regular knowledge and 11 percent presented a high level of knowledge. After the application of the Educational program, 19 percent of mothers presented a level of regular knowledge and 81 percent, a high level. The educational program was effective, achievement that mothers who participated in the study will increase their level of knowledge about healthy eating.